Busulphan lung - Littler, W. A. (Thorax, 1969)
A 61-year-old man with chronic myeloid leukaemia was treated with busulphan (Myleran). After receiving 1 g. of this drug over a period of 20 months he became dyspnoeic and developed crepitations in the lungs. Two months later radiographs of the chest revealed peri-hilar infiltrates and subsequently diffuse mottling throughout both lungs. Lung function tests showed a gross impairment of the transfer factor to a quarter of the predicted normal. At necropsy the lungs showed a striking proliferation of granular pneumocytes, many of which had disintegrated to produce intra-alveolar debris, some of which showed organization by fibrous tissue. There was associated interstitial pulmonary fibrosis. Electron microscopy confirmed the desquamated alveolar cells to be type II (granular) pneumocytes containing characteristic lamellar bodies. Many of these osmiophilic bodies, believed to be the source of pulmonary surfactant, had been liberated into the alveolar spaces, with the formation of phospholipid myelin figures and lattices. We think that the basic pathology of busulphan lung is a chemically induced alveolitis with proliferation of granular pneumocytes followed by fibrosis of alveolar walls and intra-alveolar contents. IMAGES: